2016
DOI: 10.1039/c6dt00748a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and extraction studies with a rationally designed diamide ligand selective to actinide(iv) pertinent to the plutonium uranium redox extraction process

Abstract: A new class of conformationally constrained oxa-bridged tricyclo-dicarboxamide (OTDA) ligand was rationally designed for the selective extraction of tetravalent actinides pertinent to the Plutonium Uranium Redox EXtraction (PUREX) process. Two of the designed diamide ligands were synthesized and extraction studies were performed for Pu(iv) from HNO3 medium. The mechanism of extraction was investigated by studying various parameters such as feed HNO3, NaNO3 and OTDA concentrations. The nature of the extracted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…The TG–DSC curve of the ETA is shown in Figure , which indicated that the thermal decomposition occurred at 390 K because of its structure and was consistent to 389–391 K in the literature . XRD characterization results indicated that all samples had the same identical characteristic peaks and did not exist in crystalline transformation from Figure .…”
Section: Results and Discussionsupporting
confidence: 79%
“…The TG–DSC curve of the ETA is shown in Figure , which indicated that the thermal decomposition occurred at 390 K because of its structure and was consistent to 389–391 K in the literature . XRD characterization results indicated that all samples had the same identical characteristic peaks and did not exist in crystalline transformation from Figure .…”
Section: Results and Discussionsupporting
confidence: 79%
“…In light of this, researchers have increasingly used amide-based extractants such as N , N -dihexyl octyl amide, 31 N , N , N ′, N ′-tetraoctyl diglycolamide, 12,32,33 and oxa-bridged bicyclo-dicarboxamide. 34 These extractants not only align with the CHON principle but also offer benefits such as simple synthesis and good chemical irradiation stability. Additionally, the extraction efficiency of amide extractants can be enhanced by modulating the side chains on the nitrogen atoms or the alkyl chains on the amide oxygen atoms.…”
Section: Introductionmentioning
confidence: 94%
“…42,43 Therefore, by using PSM strategy various organic functionalities (hard bases) can be incorporated in the pristine MOF to get the efficient extraction of U(VI) (hard acid) from aqueous medium. 44 In the last few years, iso-reticular metal-organic framework-3 (IRMOF-3) has been widely used for various applications such as heterogeneous catalysis, 45 gas storage/separation, 46 membranes, 47 and sensing of various metal ions, 48 due to its high surface area (BET reports 2200 m 2 g À1 ), stability towards atmosphere, high temperatures ($400 C) and its high luminescence property. Recently, the work carried out in our laboratory revealed the utility of PSM UiO-66-NH 2 graed with various functionalities for extraction of U(VI) from the aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“… 42,43 Therefore, by using PSM strategy various organic functionalities (hard bases) can be incorporated in the pristine MOF to get the efficient extraction of U( vi ) (hard acid) from aqueous medium. 44 …”
Section: Introductionmentioning
confidence: 99%